PENGARUH PROSES HARDENING BAJA AISI 1045 TERHADAP SIFAT KEAUSAN - Yosyi Mustafa Rachman; Ahmad Maulana; Fatimah Dian Ekawati (Jurnal Ilmiah Teknik Mesin, 2020)
AISI 1045 steel is a steel classified as medium carbon alloy steel which is widely used as the main material in machinery so it must have good mechanical properties such as hardness, wear resistance. The purpose of this study was to determine the effect of heat treatment on the wear rate of AISI 1045 steel. The research method used was AISI 1045 steel which was given a hardening heat treatment with a temperature variation of 800ºC, 850ºC, 900ºC with a holding time of 60 minutes, followed by rapid cooling using water . after that the specimen will be tested for wear by using a standard Pin On Disc. the results of the study show that the wear value at 800ºC has an average wear value of 15.0762 mg / cm², then at a temperature of 850ºC has an average wear value of 11.33933 mg / cm² and at a temperature of 900ºC has an average wear value of 9 9488 mg / cm². In conclusion, there was a very strong influence on the use of hardening temperature variations on the AISI 1045 steel wear and the smallest wear value on the specimen given by the hardening process at 900ºC with an average wear value of 9.9488 mg / cm².